Human capital spillovers from special economic zones: Evidence from Yangtze Delta in China - Zhaoying Lu (Economies, 2022)
This paper evaluates the effects of a place-based program in the Yangtze Delta of China-Special Economic Zones (SEZs). Taking into account spatial proximity, this paper quantifies the spillover effects of the human capital in SEZs. One major finding is that regional productivity benefits from the human capital in SEZs. The spillover effects are not only confined to their own counties, but also neighboring counties. SEZs contribute more to the regional productivity of neighboring counties than the one of the hosting county itself. Moreover, positive spillover effects of the human capital in SEZs still hold for the growth of regional productivity.
Keywords: 330; human capital; spatial analysis; special economic zone; spillovers; Yangtze Delta